2020
DOI: 10.1111/ijac.13500
|View full text |Cite
|
Sign up to set email alerts
|

Yb2O3‐Gd2O3 codoped strontium zirconate composite ceramics for potential thermal barrier coating applications

Abstract: Strontium zirconate (SrZrO3) has been considered as a promising thermal barrier coating (TBC) material for application in gas turbine engines; however, the phase transition problem limits its application. In this study, an Yb2O3 and Gd2O3 codoped SrZrO3 system with excellent properties was reported. Yb2O3‐Gd2O3 codoped SrZrO3 ceramic powders [Sr0.8(Zr0.9Yb0.05Gd0.05)O2.75, SZYG/YGZO], [Sr(Zr0.9Yb0.05Gd0.05)O2.95, SZYG] and pure SrZrO3 (SZO) powders were produced by a conventional solid‐state reaction method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Therefore, after a long time of heat treatment at 1400 • C, the material gradually transforms to a more stable structure, causing the B-site elements (Yb 3+ , Y 3+ , Gd 3+ ) precipitated in the ceramic as a secondary phases (AB 2 O 4 solid solution). 19 With an increase of annealing time, the relative contents of the second phase have increased gradually, but no new phase is formed.…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, after a long time of heat treatment at 1400 • C, the material gradually transforms to a more stable structure, causing the B-site elements (Yb 3+ , Y 3+ , Gd 3+ ) precipitated in the ceramic as a secondary phases (AB 2 O 4 solid solution). 19 With an increase of annealing time, the relative contents of the second phase have increased gradually, but no new phase is formed.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…However, the operating temperature of YSZ coating is generally limited to less than 1200 • C because of the phase transformation and coating sintering at high temperature. [18][19][20] Therefore, in order to meet the requirements of turbine blades for higher operating temperatures, more and more researchers have focused on the development of new TBCs materials with ultrahigh temperature stability and high thermal insulation. 21 Perovskites are usually characterized by high melting point, low thermal conductivity, and high thermal expansion coefficient (TEC), which have been considered potential TBCs materials.…”
Section: Introductionmentioning
confidence: 99%
“…The Yb 2 O 3 -Gd 2 O 3 co-doped YSZ coating has a relatively low thermal conductivity of 1.1 W/(m·K) (at 1100 °C). Zhang et al [ 28 ] prepared Yb 2 O 3 and Gd 2 O 3 co-doped SrZrO 3 system with good properties through a traditional solid-state reaction. The SZYG/YGZO composite ceramics with Yb 0.5 Zr 0.5 O 1.75 and SZO phases possessed a thermal conductivity of 1.3 W/(m·K) (at 1000 °C), which was 40% less than the SZO ceramics’ at least.…”
Section: Introductionmentioning
confidence: 99%
“…However, how does the added Gd 2 O 3 enhance the material properties used in TBCs? This requires the properties of the pure Gd 2 O 3 , while there are few reports on the properties of Gd 2 O 3 [ 19 , 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 ]. By consulting the relevant literature [ 19 , 21 , 22 , 29 ], it can be found that there are no detailed values for the thermal physical properties, including the thermal conductivity and thermal expansion coefficient, as well as mechanical properties, including elastic modulus, hardness and fracture toughness of the pure Gd 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Oxide co-dopped yttria stabilized zirconia ceramic material can change the structure of the thermal barrier coating system to make it a stable structure. In addition, Gd and Yb elements have a strong adsorption capacity for other elements, high chemical stability, and can be dissolved in a limited solid solution of ZrO 2 [ 27 , 28 , 29 , 30 ]. Therefore, the addition of Gd and Yb elements may greatly improve the performance of ZrO 2 thermal barrier coatings.…”
Section: Introductionmentioning
confidence: 99%